Experimental analysis of reinforced concrete beams strengthened in bending with carbon fiber reinforced polymer - VIEIRA,M. M. (2016)
The use of carbon fiber reinforced polymer (CFRP) has been widely used for the reinforcement of concrete structures due to its practicality and versatility in application, low weight, high tensile strength and corrosion resistance. Some construction companies use CFRP in flexural strengthening of reinforced concrete beams, but without anchor systems. Therefore, the aim of this study is analyze, through an experimental program, the structural behavior of reinforced concrete beams flexural strengthened by CFRP without anchor fibers, varying steel reinforcement and the amount of carbon fibers reinforcement layers. Thus, two groups of reinforced concrete beams were produced with the same geometric feature but with different steel reinforcement. Each group had five beams: one that is not reinforced with CFRP (reference) and other reinforced with two, three, four and five layers of carbon fibers. Beams were designed using a computational routine developed in MAPLE software and subsequently tested in 4-point points flexural test up to collapse. Experimental tests have confirmed the effectiveness of the reinforcement, ratifying that beams collapse at higher loads and lower deformation as the amount of fibers in the reinforcing layers increased. However, the increase in the number of layers did not provide a significant increase in the performance of strengthened beams, indicating that it was not possible to take full advantage of strengthening applied due to the occurrence of premature failure mode in the strengthened beams for pullout of the cover that could have been avoided through the use of a suitable anchoring system for CFRP.